The verse of preserving money and not transgressing in Surat Al-Nisa: An analytical study - Al-Khawaldeh, Ahmed Mohamed Ahmed; Al-Nuseirat, Jihad Muhammad Faisal (Journal of Islamic Sciences, 2023)
The aim of this research is to study the verse of saving money and not transgression in Surat An-Nisa "An Analytical Study", and the indication of the increase in the understanding of the words, meanings, rulings, and secrets of the Noble Qur’an, by extrapolating its vocabulary and structures, material, and formula, clarifying the Qur’anic readings, parsing what needs to be the syntax. This paper has followed the inductive approach and the deductive approach, and the research concluded with a set of results, the most important of which are: The noble verse urged attention to preserving money, and not to aggression because that is a requirement of faith, and that the exception in his saying: "but trade", cut off; Which was different from others, as trade was not included in the wealth that was eaten unjustly. The reading of Al-Hasan (Kill them) came to assertion. In it, there is emphasis and exaggeration in the prohibition and veneration of this matter, and the occurrence of (was) permanently in the language of the Arabs, The verse also used the verb form (the Merciful) in the sense of an active agent, with the intention of exaggerating mercy, and the Qur’an was revealed in the language of the Arabs, so it conveyed it to what befits the attributes of God. And that God Almighty is more merciful to mankind than themself.